Rediscovering Roger's self theory and personality - Ismail, Nik Ahmad Hisham; Teke, Mustafa (Jurnal Universiti Ahmad Dahlan Indonesia, 2015)
This study examined the self theory of Carl Rogers in depth. There are some important concepts illuminated well, considering one's personality development. Its main focus was positive regard, self-worth and actualizing tendency, proposed by Rogers. To explain them in brief, positive regard was studied through self-image, ideal self and congruence. Self-worth is described as conditional and unconditional to cope with challenges in life, tolerate failures and sadness at times. Actualizing tendency was expounded into fully functioning or selfactualizing. These all concepts indicated that having a tendency on human behavior and concentrating on the capacity of individuals to think intentionally and soundly, to control their biological urges, are significantly main elements to evaluate one’s self. Therefore, in the humanistic perspective, individuals have the opportunity and will to change their states of mind and behavior. This study might be a guide to some certain aspect of self related studies for other researchers to benefit accordingly and also to develop a new scale related to self using Rogers’s theory.